2020
DOI: 10.2147/dddt.s258368
|View full text |Cite
|
Sign up to set email alerts
|

<p>Novel Fast and Reliable Method for Nano-Erythrosome Production Using Shear Force</p>

Abstract: Purpose The production of nano-erythrosomes (NEs) by extrusion, which is considered the “gold standard”, has several disadvantages such as difficult equipment assembly, long procedure time, variable pressure, and problems with sterility. An alternative approach, using ultrasound probe, has been shown to overheat the sample and have suboptimal results compared to the extrusion method. In our study, we propose, develop, and test a new method for the fabrication of NEs based on shear force and then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…From confocal microscopy, we can demonstrated that the loaded drugs can extravasate via the tumor vessel and penetrate deeply into the tumor [74]. Simple methods, like shear force, can get nanoscale vesicles [41,79,80]. The nano RDVs have intact membrane proteins and glycolipids, exhibiting better stability than single liposomes.…”
Section: Rbc-derived Vesicles In Delivery Systemmentioning
confidence: 99%
“…From confocal microscopy, we can demonstrated that the loaded drugs can extravasate via the tumor vessel and penetrate deeply into the tumor [74]. Simple methods, like shear force, can get nanoscale vesicles [41,79,80]. The nano RDVs have intact membrane proteins and glycolipids, exhibiting better stability than single liposomes.…”
Section: Rbc-derived Vesicles In Delivery Systemmentioning
confidence: 99%